Genotype scores in energy and iron-metabolising genes are higher in elite endurance athletes than in nonathlete controls - Delgado, D. V.; Tellería Orriols, J. J.; Monge Martín, D.; Del Coso, J. (Applied Physiology, Nutrition, and Metabolism, 2020)
Information about the association of energy and iron-metabolising genes with endurance performance is scarce. The objective of this investigation was to compare the frequencies of polymorphic variations of genes involved in energy generation and iron metabolism in elite endurance athletes versus nonathlete controls. Genotype frequencies in 123 male elite endurance athletes (75 professional road cyclists and 48 elite endurance runners) and 122 male nonathlete participants were compared by assessing 4 genetic polymorphisms: AMPD1 c.34C/T (rs17602729), PPARGC1A c.1444G/A (rs8192678) HFEH63D c.187C/G (rs1799945) and HFEC282Y c.845G/A (rs1800562). A weighted genotype score (w-TGS; from 0 to 100 arbitrary units (a.u.)) was calculated by assigning a corresponding weight to each polymorphism. In the nonathlete population, the mean w-TGS value was lower (39.962 ± 14.654 a.u.) than in the group of elite endurance athletes (53.344 ± 17.053 a.u). The binary logistic regression analysis showed that participants with a w-TGS > 38.975 a.u had an odds ratio of 1.481 (95% confidence interval: 1.244-1.762; p < 0.001) for achieving elite athlete status. The genotypic distribution of polymorphic variations involved in energy generation and iron metabolism was different in elite endurance athletes vs. controls. Thus, an optimal genetic profile in these genes might contribute to physical endurance in athlete status.